2022
DOI: 10.1155/2022/3727165
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis of Mechanism of Influence of CRY2 on the Differentiation of Mouse Osteoblast through the Regulation of Wnt/Β-Catenin Signaling Pathway

Abstract: Noncoding RNAs were discovered to control a variety of developmental mechanisms, including osteogenesis. According to emerging evidence, cryptochrome circadian-regulating (CRY) proteins have emerged as essential controllers of osteoblast differentiation. The linked processes, on the other hand, are still unknown. The specific process that underpins osteoblast differentiation and proliferation is yet unknown. This research gives a meta-analysis of CRY2’s impact on mouse osteoblast differentiation via the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%